Conceitos de cinemática apoiados na metodologia PEER instruction para alunos de EJA - Ramalho, Ronildo de Andrade (2019)
Today, professionals in the field of education are increasingly challenged in science education, especially in physics education at all levels, fundamental, middle and higher levels. There are great challenges to overcome so that the quality of teaching at these levels is achieved. The teaching of physics in youth and adult education (EJA) proposes an even greater setback than regular education, since the classes have very different age groups, have students who do not enter a classroom for more than 20 years and many other situations that tend to stifle teaching in the EJA. Due to this diversity both in the students' age range and in their professional and life experiences, we chose to develop a method of applying the concepts of kinematics which privileged the student as an active figure within learning. For a more conceptual approach than mathematics, we use the Peer Instruction (PI) methodology of Professor Eric Mazur of Harvard University, which works mainly with conceptual tests and interaction between groups or pairs of students. The application of this methodology will help the development of reading activities that aim to collaborate to understand the concepts that will be approached in conceptual tests. It is expected that when applying this methodology, the student of EJA will be able to understand the most fundamental concepts of kinematics and to operationalize them mathematically. This methodological application will be developed in two first-year high school classes of the EJA and the results will be compared to a first-year high school class of the same modality in which there will be no type of interactive engagement, IE, will not be applied to methodology. The results should be evaluated from the Hake normalized gains study. In addition, we will use other literature at the national level to make comparisons and verify the effectiveness of the application of this methodology in Brazil.